3D-printing pen from valorization of pine cone residues as reinforcement in acrylonitrile butadiene styrene (ABS): Microstructure and thermal properties. (February 2023) - Costa, Isabella LM; Pereira, Paulo HF; Claro, Amanda Maria; Amaral, Nayara Cavichiolli do; Barud, Hernane da Silva; Ribeiro, Rosinei Batista; Mulinari, Daniella Regina
This study presents an alternative to reducing solid waste, improving the concept of green composites. So, the use of fibers from pine cone as reinforcement in acrylonitrile butadiene styrene (ABS) composites filaments as a potential for 3D pen was evaluated. The effect of the treatment chemical (alkaline and bleaching) was studied. A thermokinetic mixer processed the ABS/pine cone fibers (2 and 5% wt.) composites. After, the filaments were prepared by mini extruder and printing 3D pen. Filaments were characterized by Scanning Electron Microscopy (SEM), Thermogravimetry (TGA), and Infrared Spectroscopy (FTIR). Filaments revealed homogeneous diameters. The addition of 2 and 5% wt. fiber not significantly influenced the filament's diameter and density. On the other hand, thermal stability and morphological analysis influenced the type of fiber (raw, treated, and bleached). The addition of bleached fibers to ABS increased composites' thermal stability compared to other fibers (treated and raw). Also, inserting bleached fibers was perceptible a uniformly distributed and embedded throughout the wire cross-section compared to treated and raw fiber added to ABS due to good interfacial bonding. Results indicated that fibers were hydrogen-bonded to ABS chains and increased the filament's density. So, it is possible to affirm that the addition of fibers from pine cone to ABS thermally improved and can be a low-cost feedstock for printing 3D pen applications. Despite the low concentration of natural fiber on the composites investigated in this work, the successful obtainment of ABS reinforced with biodegradable natural fiber, compromising neither its thermal properties nor its processability and printability, opens the possibility for future work investigation into a composite with larger fiber content.